Faktor-faktor yang Memengaruhi Literasi Keuangan Mahasiswa Pendidikan Ekonomi FKIP Universitas Sebelas Maret Surakarta - Shafira Ika Rahmayani; Sudarno Sudarno; Khresna Bayu Sangka (Universitas Negeri Surabaya, 2022)
This study aims to determine the formation of new factors from five dimensions, there are knowledge of financial concepts, communication skills related to finance, personal abilities in managing finances, ability to make financial decisions and commitment to the future in students of Economics Education FKIP Sebelas Maret University. Proportionate stratified random sampling method used in this study with 117 students as the sample. Data collection method using a questionnaire then analyzed by Exploratory Factor Analysis. The results show that there is new formation of new factors from five dimensions that influenced student’s financial literacy, which consisted of 9 factors including (1) Use of Technology, (2) Level of Interest and Involvement, (3) Financial Attitude and Behavior, (4) Campus Involvement, (5) Level of Confidence, (6) Parental Involvement, (7) Financial Learning, (8) Trust in Payment, (9) The Habit of Giving. There are several weaknesses in this study, future researchers are expected to improve the question instrument to find out a more in-depth picture of the factors that affect student’s financial literacy.